Weighted Neutrosophic Soft Multiset and Its Application to Decision Making - Granados, Carlos; Das, Ajoy K.; Osu, Bright O. (Yugoslav Journal of Operations Research, 2022)
In this paper, we procure the idea of weighted neutrosophic soft multiset (WNSMS) as a generalization of neutrosophic soft multiset (NSMS) and its basic properties are to be showed. Besides, we present a new adjustable approach to WNSMS based on decision-making, for solving decision-making in an indeterminacy situation.